Modelo de predição para o crescimento de hidratos em paredes de tubulações - Gans, Luiz Henrique Accorsi (2016)
The study of the clathrate-hydrate formation processes in pipelines is very important to the oil and gas industry because these structures can stop production and it represents a safety risk due to the pressure build-up in the pipelines. Several research groups have proposed different models to predict how a hydrate film grows. However, the models based only on heat transfer could not explain satisfactorily the experimental data because the water and gas consumption were disregarded. So, in order to predict the hydrate growth phenomenon in tube wall, the current work presents a mathematical and numerical model for the coupled mass and energy balance problem for CO2 and CH4 hydrates. As a result of the coupling equations, no analytical solution is possible. So, a computational algorithm has been proposed based on the finite volume method and fully implicit scheme. The verification of the code was conducted through a dissociation model which has been presented by the literature. Although, its validation was not possible since no experimental data is currently available. The hydrate growth rate was evaluated by studying the influence of the thermodynamic conditions, the hydrate porosity and thermal conductivity, the pipe diameter and the gas availability. As a result, it has been noticed that the hydrate porosity and the gas availability had great influence in the hydrate growth rate.